(untitled) (Bangladesh Journal of Urology, 2020)
Objectives: To compare pain, systemic lidocaine toxicity and complications between periprostatic with intraprostatic local anaesthesia for transrectal prostate biopsy. Methods: This study was carried out in the Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka Medical College (DMCH) and Comfort Nursing Home, Dhaka during the period of January 2009 to October 2009, For this purpose, a total number of 60 consecutive patients having increased prostate specific antigen (PSA >4.0ng/ml), abnormal DRE/transrectal ultrasound were admitted in the above mentioned hospitals were enrolled in this study for surgical management. Results: The age ranged from 50 to 90 years and the maximum number was found in the age group of 61-70 years in both groups. The mean(±SD) age was 68.5±7.5 years and 70.3±8.2 years in group I and group II respectively. The mean(±SD) PSA was 17.0±12.8ng/ ml with their PSA ranged from 5.9- 62.8ng/ml in group I and in group II was 17.2±17.3ng/ml with their PSA ranged from 4.6 – 55.1ng/ml, which was not significant (p>0.05) between two groups. Normal digital rectal was found 14(46.7%) and 16(53.3%) in group I and group II respectively. Carcinoma was found 13(43.3%) and 14(46.7%) in group I and group II respectively and rest of them were benign in group I and group II respectively. The mean(±SD) pain degree during biopsy was 2.6±1.1 and 2.0±1.2 in group I and group II respectively according to allocated pain score. Pain degree after 30 minutes of biopsy, most of the patients had no pain in both groups. Pain during anesthesia it was found that 4(13.3%) and 13(43.3%) of the patients had no pain in group I and group II respectively. The mean(±SD) pain degree during anesthesia was 2.7±1.2 and 2.1±1.2 in group I and group II respectively. Conclusion: It is a simple and safe method that is less painful and it should be considered in all patients undergoing transrectal ultrasound guided prostate biopsy. The decreased discomfort of this procedure may enable more core biopsies to be taken in patients at high risk for prostate cancer or in those with an enlarged prostate Bangladesh Journal of Urology, Vol. 15, No. 2, July 2012 p.33-39